(* Title: HOL/Isar_Examples/Fibonacci.thy Author: Gertrud Bauer Copyright 1999 Technische Universitaet Muenchen The Fibonacci function. Original tactic script by Lawrence C Paulson. Fibonacci numbers: proofs of laws taken from R. L. Graham, D. E. Knuth, O. Patashnik. Concrete Mathematics. (Addison-Wesley, 1989) *) section ‹Fib and Gcd commute› theory Fibonacci imports "HOL-Computational_Algebra.Primes" begin text_raw ‹⁋‹Isar version by Gertrud Bauer. Original tactic script by Larry Paulson. A few proofs of laws taken from \<^cite>‹"Concrete-Math"›.›› subsection ‹Fibonacci numbers› fun fib :: "nat ⇒ nat" where "fib 0 = 0" | "fib (Suc 0) = 1" | "fib (Suc (Suc x)) = fib x + fib (Suc x)" lemma [simp]: "fib (Suc n) > 0" by (induct n rule: fib.induct) simp_all text ‹Alternative induction rule.› theorem fib_induct: "P 0 ⟹ P 1 ⟹ (⋀n. P (n + 1) ⟹ P n ⟹ P (n + 2)) ⟹ P n" for n :: nat by (induct rule: fib.induct) simp_all subsection ‹Fib and gcd commute› text ‹A few laws taken from \<^cite>‹"Concrete-Math"›.› lemma fib_add: "fib (n + k + 1) = fib (k + 1) * fib (n + 1) + fib k * fib n" (is "?P n") ― ‹see \<^cite>‹‹page 280› in "Concrete-Math"›› proof (induct n rule: fib_induct) show "?P 0" by simp show "?P 1" by simp fix n have "fib (n + 2 + k + 1) = fib (n + k + 1) + fib (n + 1 + k + 1)" by simp also assume "fib (n + k + 1) = fib (k + 1) * fib (n + 1) + fib k * fib n" (is " _ = ?R1") also assume "fib (n + 1 + k + 1) = fib (k + 1) * fib (n + 1 + 1) + fib k * fib (n + 1)" (is " _ = ?R2") also have "?R1 + ?R2 = fib (k + 1) * fib (n + 2 + 1) + fib k * fib (n + 2)" by (simp add: add_mult_distrib2) finally show "?P (n + 2)" . qed lemma coprime_fib_Suc: "coprime (fib n) (fib (n + 1))" (is "?P n") proof (induct n rule: fib_induct) show "?P 0" by simp show "?P 1" by simp fix n assume P: "coprime (fib (n + 1)) (fib (n + 1 + 1))" have "fib (n + 2 + 1) = fib (n + 1) + fib (n + 2)" by simp also have "… = fib (n + 2) + fib (n + 1)" by simp also have "gcd (fib (n + 2)) … = gcd (fib (n + 2)) (fib (n + 1))" by (rule gcd_add2) also have "… = gcd (fib (n + 1)) (fib (n + 1 + 1))" by (simp add: gcd.commute) also have "… = 1" using P by simp finally show "?P (n + 2)" by (simp add: coprime_iff_gcd_eq_1) qed lemma gcd_mult_add: "(0::nat) < n ⟹ gcd (n * k + m) n = gcd m n" proof - assume "0 < n" then have "gcd (n * k + m) n = gcd n (m mod n)" by (simp add: gcd_non_0_nat add.commute) also from ‹0 < n› have "… = gcd m n" by (simp add: gcd_non_0_nat) finally show ?thesis . qed lemma gcd_fib_add: "gcd (fib m) (fib (n + m)) = gcd (fib m) (fib n)" proof (cases m) case 0 then show ?thesis by simp next case (Suc k) then have "gcd (fib m) (fib (n + m)) = gcd (fib (n + k + 1)) (fib (k + 1))" by (simp add: gcd.commute) also have "fib (n + k + 1) = fib (k + 1) * fib (n + 1) + fib k * fib n" by (rule fib_add) also have "gcd … (fib (k + 1)) = gcd (fib k * fib n) (fib (k + 1))" by (simp add: gcd_mult_add) also have "… = gcd (fib n) (fib (k + 1))" using coprime_fib_Suc [of k] gcd_mult_left_right_cancel [of "fib (k + 1)" "fib k" "fib n"] by (simp add: ac_simps) also have "… = gcd (fib m) (fib n)" using Suc by (simp add: gcd.commute) finally show ?thesis . qed lemma gcd_fib_diff: "gcd (fib m) (fib (n - m)) = gcd (fib m) (fib n)" if "m ≤ n" proof - have "gcd (fib m) (fib (n - m)) = gcd (fib m) (fib (n - m + m))" by (simp add: gcd_fib_add) also from ‹m ≤ n› have "n - m + m = n" by simp finally show ?thesis . qed lemma gcd_fib_mod: "gcd (fib m) (fib (n mod m)) = gcd (fib m) (fib n)" if "0 < m" proof (induct n rule: nat_less_induct) case hyp: (1 n) show ?case proof - have "n mod m = (if n < m then n else (n - m) mod m)" by (rule mod_if) also have "gcd (fib m) (fib …) = gcd (fib m) (fib n)" proof (cases "n < m") case True then show ?thesis by simp next case False then have "m ≤ n" by simp from ‹0 < m› and False have "n - m < n" by simp with hyp have "gcd (fib m) (fib ((n - m) mod m)) = gcd (fib m) (fib (n - m))" by simp also have "… = gcd (fib m) (fib n)" using ‹m ≤ n› by (rule gcd_fib_diff) finally have "gcd (fib m) (fib ((n - m) mod m)) = gcd (fib m) (fib n)" . with False show ?thesis by simp qed finally show ?thesis . qed qed theorem fib_gcd: "fib (gcd m n) = gcd (fib m) (fib n)" (is "?P m n") proof (induct m n rule: gcd_nat_induct) fix m n :: nat show "fib (gcd m 0) = gcd (fib m) (fib 0)" by simp assume n: "0 < n" then have "gcd m n = gcd n (m mod n)" by (simp add: gcd_non_0_nat) also assume hyp: "fib … = gcd (fib n) (fib (m mod n))" also from n have "… = gcd (fib n) (fib m)" by (rule gcd_fib_mod) also have "… = gcd (fib m) (fib n)" by (rule gcd.commute) finally show "fib (gcd m n) = gcd (fib m) (fib n)" . qed end